2020
DOI: 10.3390/ijerph17072358
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Determinants of the Severity of Pedestrian Injuries by Pedestrian Age: A Case Study of Daegu Metropolitan City, South Korea

Abstract: Pedestrian-vehicle crashes can result in serious injury to pedestrians, who are exposed to danger when in close proximity to moving vehicles. Furthermore, these injuries can be considerably serious and even lead to death in a manner that varies depending on the pedestrian’s age. This is because the pedestrian’s physical characteristics and behaviors, particularly in relation to roads with moving vehicles, differ depending on the pedestrian’s age. This study examines the determinants of pedestrian injury severi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 44 publications
2
7
0
Order By: Relevance
“…During the collisions due to vehicle impact, the engine sometimes may catch fire, which can spread quickly to the entire vehicle, preventing quick rescue operations from evacuating drivers and passengers, who succumb to death [ 100 ]. Pedestrians are classified among the vulnerable road users’ group, are directly exposed to impact, which increases the chances of fatalities [ 101 , 102 ]. The observation that collisions between motor vehicles lower the probability of severe injuries may seem contradictory in light of existing research; however, it is worth mentioning that the majority of crashes reported for the current study were rear-ended, which mainly occurred along divided highways and expressways.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the collisions due to vehicle impact, the engine sometimes may catch fire, which can spread quickly to the entire vehicle, preventing quick rescue operations from evacuating drivers and passengers, who succumb to death [ 100 ]. Pedestrians are classified among the vulnerable road users’ group, are directly exposed to impact, which increases the chances of fatalities [ 101 , 102 ]. The observation that collisions between motor vehicles lower the probability of severe injuries may seem contradictory in light of existing research; however, it is worth mentioning that the majority of crashes reported for the current study were rear-ended, which mainly occurred along divided highways and expressways.…”
Section: Resultsmentioning
confidence: 99%
“…During the collisions due to vehicle impact, the engine sometimes may catch fire, which can spread quickly to the entire vehicle, preventing quick rescue operations from evacuating drivers and passengers, who succumb to death [100]. Pedestrians are classified among the vulnerable road users' group, are directly exposed to impact, which increases the chances of fatalities [101,102].…”
Section: Sensitivity Analysis For Crash Characteristicsmentioning
confidence: 99%
“…Different risk factors (such as demographics, crash, and built environment characteristics) that affect pedestrian crash injury severity and casualty have been identified by several studies [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. From the demographic perspective, males and the elderly are found to be more prone to incur serious injuries and fatalities than other age groups when involved in pedestrian crashes [ 16 , 17 , 29 , 30 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, studies suggest that there is a higher risk of crashes with fatal and severe injury outcomes in areas with higher population density, in which pedestrians are more exposed to crashes [ 5 , 16 ]. Public transportation accessibility has been associated with pedestrian crash injury severity, suggesting the need of safety zones near bus stops and subway stations to protect pedestrians [ 15 , 23 , 44 , 45 ]. Finally, studies have concluded that pedestrians suffer more severe injuries at road intersections due complex traffic operations inherent to such intersections [ 3 , 21 , 36 , 46 , 47 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Table 3 summarizes the four variables considered and the frequency of occurrence in each of their states. Some variables, such as vehicle type, pedestrian age, pedestrian gender, accident location, pavement and road type, among others, are extensively studied to understand pedestrian degree of injury, as for example in the study by Seung-Hoon Park and Min-Kyung Bae [21] to analyse the pedestrian degree of injury rates by age group.…”
Section: Study Variablesmentioning
confidence: 99%